Positive Correlations Between Presence of Gram Negative Enteric Rods and Porphyromonas Gingivalis in Subgingival Plaque (2011)
ABSTRACT: The association between Gram negative enteric rods and Porphyromonas gingivalis in periodontal diseases has received little attention in the literature. Thus, the aim of this study was to investigate the associations between Gram negative enteric rods, Porphyromonas gingivalis and clinical parameters of periodontal disease. The prevalence of Gram-negative enteric rods and P. gingivalis were examined in patients with chronic periodontitis. Chi-square and Mann-Whitney tests were used to determine differences in clinical variables versus the presence or absence of both microorganisms. Correlations of both organisms and clinical data were determined using Spearman rank correlation coefficient. Gram-negative enteric rods and P. gingivalis were detected in 20 (26.3%) and 51 (67.1%) subjects, respectively. A total 17 (22.4%) individuals harbored both microorganisms studied. There were significantly positive correlations between enteric rods and presence of P. gingivalis (r=0.531, P<0.0001). Both microorganisms were significantly and positively correlated with probing depth, clinical attachment level and bleeding on probing (P<0.0001). The mean probing depth (mm) of the sampled sites was significantly deeper in patients with presence of P. gingivalis and Gram-negative enteric rods. This study suggests that the presence of Gram negative enteric rods and P. gingivalis is related to adverse periodontal conditions. These results could have an impact on periodontal treatment and should be taken into account in the mechanical and antimicrobial treatment of periodontal disease in some populations.